The Influence of Discipline and Compensation on Employees Performance at PT. Federal International Finance (FIF Group) Sawahan - Sonya Nurfalia; Afriyeni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to test the discipline and compensation variable influence of PT. Federal International Finance (FIFGROUP) Sawahan's employees performance. The types of this study is quantitative research with the employees of PT. FIF Sawahan as sample population. The data collection is carried out by questionnaire to the 40 employees using saturated sampling technique which are all of population members are sample. This data is analyzed using multiple linear regression with the SPSS software. The results of this study indicate that the discipline has the positive and significant effect on employees performance confirmed by the value of t-count is more than t-table 5,131 > 0,3081 with the significant value is less than the alpha value 0,00 < 0,05. The compensation has the positive and significant effect on employees performance confirmed by the value of t-count is more than t-table 2,430 > 0,3081 and the significant value is less than alpha value 0,020 < 0,05